Succession incentives among agricultural cooperative associates: a study in the north half of Rio Grande do Sul (Research, Society and Development, 2020)
This study aims to verify the succession perspectives of the members of Cooperativa Tritícola Sarandi Ltda. (Cotrisal), in the unit of the municipality of Palmeira das Missões (RS). The sample is random, in which 37 farmers associated with the cooperative and their respective successors were interviewed, from August to October 2019. The data were analyzed using Descriptive Statistics, with the help of Microsoft Excel. Through the analysis, it was possible to identify three groups of respondents. The first group has likely successors (nineteen respondents). The second group does not have successors on the property (eight respondents). And the third group, the children are already successors on the property (ten respondents). The results showed that in the perception of the associates, with or without successors, there are several factors that influence the permanence of children in rural areas. Among these factors is the incentive for children from an early age, income, profitability and family tradition. As for the perception of the interviewed children, among the factors that influence their permanence are permission to work on the property and support in studies / professional career. In addition, the interviewed farmers highlight the importance of diversifying agricultural activities, which result in more satisfactory incomes for young people and, consequently, their permanence in rural areas. It is concluded that, in the interviewees' perception, the decision to remain or not on the property, as successors, is linked to different factors, which are associated with the context in which the family and the rural property are inserted.